Breeding Moth Orchid (Phalaenopsis spp.) for Use in Urban Settings - Bolaños Villegas, Pablo Alberto (2025)
Orchid breeding is mostly associated with the sale of potted plants. However increasing urbanization rates across the world lead to population settlements deprived of access to nature and recreational infrastructure in general. Unfortunately, the reduced availability of parks and green spaces may cause learning and socialization impairments that severely hamper the ability to deal with the mental and emotional pressures of everyday life. By re-creating natural environments and adapting them to the needs of modern cities across the world, we may be able to design aesthetically pleasing sites that foster an appreciation of beauty, the arts, cultural heritage, and biodiversity as well as provide for relaxation and contemplation and enhance positive social interactions for everyone. This chapter discusses the technical possibilities of breeding and mass-producing Phalaenopsis orchids for landscaping in parks, vertical green walls, and indoor sites within office buildings as a tool to achieve ecological sustainability in cities. Orchids are a family of diverse plants adapted to most ecological niches, so there is great potential for widening the urban landscaping palette with Phalaenopsis and other orchid species suited to different environmental and cultural requirements.